2006
DOI: 10.1016/j.tca.2006.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of ligno-cellulosic fuels: DSC and TGA studies

Abstract: The scope of this work was to show the utility of thermal analysis and calorimetric experiments to study the thermal oxidative degradation of Mediterranean scrubs. We investigated the thermal degradation of four species; DSC and TGA were used under air sweeping to record oxidative reactions in dynamic conditions. Heat released and mass loss are important data to be measured for wildland fires modelling purpose and fire hazard studies on ligno-cellulosic fuels. Around 638 K and 778 K, two dominating and overlap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 25 publications
2
31
1
1
Order By: Relevance
“…According to Yang et al (2007) hemicelluloses presents an exothermal peak at 275 °C. Leroy et al (2006) observed an exothermal peak at 505 °C assigned to lignin degradation of four wood species from Mediterranean. In a recent study, Werner et al (2014) reported that hemicelluloses presented an endothermic peak at around 300-330 °C.…”
Section: Wood Thermal Propertiesmentioning
confidence: 98%
“…According to Yang et al (2007) hemicelluloses presents an exothermal peak at 275 °C. Leroy et al (2006) observed an exothermal peak at 505 °C assigned to lignin degradation of four wood species from Mediterranean. In a recent study, Werner et al (2014) reported that hemicelluloses presented an endothermic peak at around 300-330 °C.…”
Section: Wood Thermal Propertiesmentioning
confidence: 98%
“…The hydrochars formed are analyzed with thermogravimetric analysis (TGA) and FTIR. TGA is a common method to study biomass [11][12][13][14] and hydrochar composition [13,[15][16][17] and is here mainly used to detect residual cellulose from incomplete conversion of the biomass. Infrared spectra are often used to characterize hydrochar via the presence of characteristic, IR-active, functional groups (see for example: [18]).…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate analysis results are shown in Table 1. Before performing this analysis, peat materials were ovendried for 24 hours at 333 K [15]. The deshydrated samples were stored in airtight plastic containers and send for laboratory testing.…”
Section: Peat Samplesmentioning
confidence: 99%
“…In this study, the pyrolytic behaviour of the different kinds of peats was investigated with a thermogravimetric analyzer (Pyris® 1 TGA Perkin Elmer®) in air atmosphere (30 mL/min) at temperatures ranging from 500 to 900 K. As the study was focused on thermal degradation samples were oven-dried for 24 hours at 333 K [15]. Dry samples were then kept to the desiccator to preserve samples from ambient air humidity.…”
Section: Thermal Analysis and Kinetic Backgroundmentioning
confidence: 99%